Everyday Kitchen for Kids : 100 Amazing Savory and Sweet Recipes Children Can Really Make - Low, Jennifer; Szulc, Ryan (Vancouver, BC : Whitecap Books, 2012)
A collection of recipes for children to prepare.
Keywords: Cooking -- Juvenile literature; Cooking; Cookbooks